Silver-based composite catalyst and preparation method and application thereof

Through the composite catalyst of silver and thiol-modified silver sulfide and titanium dioxide, the problem of poor selectivity and stability of existing silver-based catalysts in catalyzing carbon dioxide reduction to form carbon monoxide is solved, and efficient and stable catalytic performance and highly selective carbon monoxide generation are achieved.

CN119909764APending Publication Date: 2025-05-02YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510224203.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

When existing silver-based catalysts catalyze carbon dioxide reduction to produce carbon monoxide, there are problems such as poor selectivity and stability and low energy utilization.

Method used

By combining silver and thiol-modified silver sulfide with titanium dioxide to form a silver-based composite catalyst, the synergistic effect of the thiol-modified silver sulfide and the interface site of titanium dioxide is used to regulate charge distribution and electron transfer, and improve catalytic performance.

Benefits of technology

The catalyst has achieved high reactivity and stability, good carbon dioxide reduction effect and high selectivity of carbon monoxide, and the Faraday efficiency of electrocatalytic carbon dioxide reduction reached 96.7%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909764A_ABST
    Figure CN119909764A_ABST
Patent Text Reader

Abstract

The invention discloses a silver-based composite catalyst and a preparation method and application thereof.The composite catalyst comprises Ag, sulfydryl-modified silver sulfide and titanium dioxide, the sulfydryl-modified silver sulfide and the titanium dioxide are mixed, so that the titanium dioxide is loaded on the sulfydryl-modified silver sulfide of a lamellar structure; and reducing the sulfydryl-modified silver sulfide part into Ag, and changing the color of the material from white to gray, thereby obtaining the composite catalyst. The catalyst is formed by compounding silver and sulfydryl modified silver sulfide and titanium dioxide, and the catalyst is high in catalytic reaction activity, stable in catalytic performance, good in carbon dioxide reduction effect and high in carbon monoxide selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and particularly relates to a silver-based composite catalyst and a preparation method and application thereof. Background Art

[0002] The massive consumption of traditional fossil fuels has led to a rapid increase in carbon dioxide in the atmosphere, and carbon dioxide emission reduction is imminent. Electrocatalytic carbon dioxide reduction to create valuable products has attracted widespread attention. Among the various gaseous products of carbon dioxide reduction, carbon monoxide products have a higher economic value than other products and have attracted much attention. Not only can it be mixed with hydrogen to form synthesis gas, but it is also an important raw material for the synthesis of a series of basic organic chemicals.

[0003] However, the development of efficient electrocatalytic catalysts remains a challenge. According to previous studies, metal electrodes, including silver, gold, and zinc, have a high electrocatalytic activity due to their high affinity for intermediates on the electrode surface. * The binding energy of CO) is more suitable and it is easier to desorb from the catalyst surface, so it shows better catalytic activity. Among them, silver-based catalysts have high selectivity for carbon monoxide, and their moderate price and excellent performance have attracted much attention; however, in practical applications, due to their high overpotential and interfacial competitive hydrogen evolution reaction, silver-based catalysts still face the dilemma of poor catalyst selectivity and stability and low energy utilization. Summary of the invention

[0004] Purpose of the invention: The first purpose of the present invention is to provide a silver-based composite catalyst that improves catalyst stability and selectivity for catalytic reduction of CO2 to generate CO; the second purpose of the present invention is to provide a method for preparing the silver-based composite catalyst; the third purpose of the present invention is to provide an application of the silver-based composite catalyst in catalytic reduction of CO2 to generate CO.

[0005] Technical solution: The silver-based composite catalyst of the present invention comprises Ag, thiol-modified silver sulfide and titanium dioxide. The thiol-modified silver sulfide is mixed with titanium dioxide so that titanium dioxide is loaded on the thiol-modified silver sulfide with a lamellar structure. Then, the thiol-modified silver sulfide is partially reduced to Ag, and the color of the material changes from white to gray to obtain the composite catalyst. The structural formula of the thiol-modified silver sulfide is as follows:

[0006]

[0007] Preferably, in the mixture of the mercapto-modified silver sulfide and titanium dioxide, the mass ratio of silver sulfide to titanium dioxide is 3 to 5: 2 to 4. With the addition of titanium dioxide, the synergistic effect of the mercapto-modified silver / silver sulfide and titanium dioxide interface sites adjusts the charge distribution, promotes electron transfer, and improves the catalyst's performance in catalyzing carbon dioxide to carbon monoxide, but as the amount of titanium dioxide increases, part of the active components are covered, and the catalytic performance decreases accordingly.

[0008] The method for preparing the silver-based composite catalyst of the present invention comprises the following steps:

[0009] (1) mixing a silver salt solution and a penicillamine solution to react and generate a white precipitate, which is then washed and dried to obtain thiol-modified silver sulfide;

[0010] (2) mixing thiol-modified silver sulfide and nano-titanium dioxide to obtain a white suspension;

[0011] (3) placing the white suspension obtained in step (2) under a xenon lamp light source for reaction, the white suspension slowly turns into gray to complete the reaction, washing, and drying to obtain the silver-based composite catalyst.

[0012] Preferably, in step (1), the reaction temperature is 40-60° C. and the reaction time is 60-200 min.

[0013] Preferably, in step (1), the silver salt is silver nitrate, and the concentrations of the silver nitrate solution and the penicillamine solution are both 0.2-1.5 mg / mL. An appropriate excess of penicillamine can accelerate the production of the complex.

[0014] Preferably, in step (2), the mercapto-modified silver sulfide is mixed with titanium dioxide by: mixing the mercapto-modified silver sulfide and nano-titanium dioxide and then ultrasonicating for 15 to 50 minutes.

[0015] Preferably, in step (3), the reaction is carried out at room temperature and the reaction time is 0.5 to 2 hours.

[0016] Preferably, in step (3), the cleaning comprises: rinsing with deionized water for 2 to 3 times; and the drying comprises: drying at 50 to 80° C. for 8 to 12 hours.

[0017] The silver-based composite catalyst of the present invention is used in catalyzing the reduction of CO2 to generate CO.

[0018] Preferably, the application method is: electrocatalytic reduction of carbon dioxide is carried out in an H cell, the anode compartment contains a counter electrode, the cathode compartment contains a reference electrode and a working electrode, the two compartments are separated by an anion exchange membrane, and both sides are filled with KHCO3 solution as an electrolyte;

[0019] The preparation method of the working electrode is as follows: the catalyst is dispersed in an isopropanol Nafion solution, and uniform catalyst ink is formed by ultrasound, and the catalyst ink is dropped on carbon fiber paper to form a catalyst film, which is connected with conductive glue and wires to serve as a working electrode; wherein the working electrode is prepared using the silver-based composite catalyst.

[0020] Preferably, the preparation method of the working electrode is: dispersing the silver-based composite catalyst in an isopropanol Nafion solution and ultrasonically forming a uniform catalyst ink, dropping the catalyst ink on carbon fiber paper to form a catalyst film, and connecting them with conductive glue and wires to serve as the working electrode.

[0021] Further preferably, the preparation method of the working electrode is: dispersing 0.01-2 mg of the silver-based composite catalyst in 0.1 mL of 15% isopropanol Nafion solution, and ultrasonicating for 30 minutes to form a uniform catalyst ink, and dropping the ink on 1×2 square centimeters of carbon fiber paper to form a catalyst film with an effective area of ​​1 square centimeter.

[0022] Preferably, the concentration of KHCO3 is 0.02-0.2 mol / L.

[0023] Invention mechanism: Silver is a commonly used catalyst with high catalytic performance. It can improve the carbon dioxide reduction performance by synergizing with mercapto silver sulfide. The mercapto group can promote the combination of silver ions and sulfur. The synergistic effect of the mercapto-modified silver / silver sulfide and titanium dioxide interface sites regulates the charge distribution, promotes electron transfer, and also changes the binding energy of the reaction intermediates. The modification of the mercapto group inhibits the occurrence of hydrogen evolution reaction and regulates the binding energy of the reaction intermediates. Therefore, the product selectivity is optimized, thereby obtaining a higher carbon dioxide reduction performance.

[0024] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The present invention forms a catalyst by combining silver, thiol-modified silver sulfide and titanium dioxide, which has high catalytic reaction activity, stable catalytic performance, good carbon dioxide reduction effect, and high selectivity for carbon monoxide; (2) The present invention successfully synthesizes the silver-based composite catalyst by wet chemical method and photoreduction method, and the synthesis is simple and the price is low; (3) The silver-based composite catalyst of the present invention is used for the reaction of reducing carbon dioxide to generate carbon monoxide. At a low potential of -1.3V (vs.RHE), the electrocatalytic carbon dioxide reduction of carbon monoxide has a Faraday efficiency of 96.7% and a carbon monoxide partial current of 19.3mA, which has good carbon monoxide selectivity compared with the existing catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1This is a scanning electron microscope image of the mercapto-modified silver / silver sulfide-titanium dioxide composite catalyst prepared in Example 1 of the present invention;

[0026] Figure 2 This is an XPS binding energy image of the thiol-modified silver / silver sulfide-titanium dioxide composite prepared in Example 1 of the present invention;

[0027] Figure 3 The linear voltammetric curves of the catalysts of Example 1 and Comparative Examples 1 to 4 of the present invention under different gas conditions;

[0028] Figure 4 This is a Faraday efficiency distribution diagram of the products of the mercapto-modified silver / silver sulfide-titanium dioxide composite catalyst prepared in Example 1 of the present invention at various potentials under carbon dioxide conditions. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below in conjunction with embodiments.

[0030] Example 1

[0031] The preparation method of the silver-based composite catalyst of the present invention comprises the following steps:

[0032] (1) First, prepare 30 mL of a 1 mg / mL aqueous solution of penicillamine and 20 mL of a 1 mg / mL aqueous solution of silver nitrate;

[0033] (2) gradually adding the aqueous solution of penicillamine to the stirred aqueous solution of silver nitrate, stirring and mixing to form a new solution;

[0034] (3) Then, the mixed solution obtained in step (2) was placed on a heatable stirrer, the reaction time was 120 minutes, the heating temperature was 50° C., the stirring speed was 1000 rpm, and a white precipitate was formed after chemical reaction;

[0035] (4) extracting the product in step (3), washing it with deionized water, centrifuging it three times, and drying it (in an oven at 60° C.) to obtain thiol-modified silver sulfide;

[0036] (5) Weigh 5 mg of silver sulfide and 2 mg of nano-titanium dioxide, mix them in a beaker with ultrasonic stirring for 30 minutes;

[0037] (6) placing the material obtained in step (5) under a xenon lamp light source, stirring at a speed of 500 rpm, and reacting for 1 hour. After the white suspension slowly turns gray, it is then allowed to stand for 1 hour.

[0038] (7) Finally, the product obtained in step (6) was separated, rinsed with deionized water for three times, and dried (drying temperature was 60° C., and drying time was 12 hours) to obtain a thiol-modified silver / silver sulfide-titanium dioxide composite catalyst.

[0039] Figure 1 This is a scanning electron microscope image of the mercapto-modified silver / silver sulfide-titanium dioxide composite prepared in the present invention. It can be seen from the image that the titanium dioxide particles are loaded on the smooth, flat, irregular silver sulfide flakes.

[0040] Figure 2 The XPS binding energy image of the thiol-modified silver / silver sulfide-titanium dioxide composite. The full spectrum image of the thiol-modified silver / silver sulfide-titanium dioxide composite ( Figure 2 a) shows that the catalyst is composed of silver, sulfur, titanium and oxygen. Figure 2 In b), the fitted peak at 368.1 eV corresponds to the Ag 3d 5 / 2 , while the fitted peak at 374.1 eV corresponds to Ag3d 3 / 2 , which indicates the presence of some silver ions. This is due to the strong affinity between the thiol ligand and silver, which forms an Ag-S bond between sulfur and silver. S2p diagram ( Figure 2 c) corresponds to S2p 3 / 2 The peak of also proves the existence of Ag-S bond. Figure 2 In d), Ti 2p is observed at 458.7 eV and 464.4 eV, respectively. 3 / 2 and Ti 2p 1 / 2 peak, which is attributed to the Ti-O-Ti bond, indicating that Ti 4+ It exists in the form of titanium dioxide. It can be determined that the complex is composed of silver, mercapto-modified silver sulfide and titanium dioxide.

[0041] Comparative Example 1

[0042] The preparation method of silver nanoparticles is as follows:

[0043] (1) First, prepare 50 mL of 15 mM sodium borohydride solution and 5 mL of 10 mM silver nitrate, take out 15 mL of the sodium borohydride solution and place it in an ice bath for later use;

[0044] (2) Then, 2.5 mL of 10 mM silver nitrate was added dropwise, and the mixture was stirred continuously for 10 minutes to ensure that the solution reacted evenly;

[0045] (3) After standing for 5 hours, the final product was collected, rinsed with deionized water three times, and dried (drying temperature was 60° C., and drying time was 12 hours) to obtain silver nanoparticles.

[0046] Comparative Example 2

[0047] The preparation method of silver nanoparticle-titanium dioxide is as follows:

[0048] (1) Weigh 5 mg of the silver nanoparticles obtained in Comparative Example 1 and 2 mg of nano-titanium dioxide, and mix them in a beaker by ultrasonic stirring for 30 minutes;

[0049] (2) The product obtained in the separation step (1) was rinsed with deionized water three times and dried (drying temperature was 60° C. and drying time was 12 hours) to obtain a silver nanoparticle-titanium dioxide composite catalyst.

[0050] Comparative Example 3

[0051] The preparation method of thiol-modified silver sulfide is as follows:

[0052] (1) First, prepare 30 mL of 1 mg / mL penicillamine aqueous solution and 20 mL of 1 mg / mL silver nitrate aqueous solution;

[0053] (2) gradually adding the aqueous solution of penicillamine to the stirred aqueous solution of silver nitrate, stirring and mixing to form a new solution;

[0054] (3) Then, the mixed solution obtained in step (2) was placed on a heatable stirrer, the heating temperature was 50° C., the reaction time was 120 minutes, the stirring speed was 1000 rpm, and a white precipitate was formed after chemical reaction;

[0055] (4) extracting the product in step (3), washing it with deionized water, centrifuging it three times, and drying it (in an oven at 60° C.) to obtain thiol-modified silver sulfide.

[0056] Comparative Example 4

[0057] The preparation method of silver / silver sulfide-titanium dioxide is as follows:

[0058] (1) First, prepare 50 mL of 0.7% ammonia water, 25 mL of 0.3 mol / L silver nitrate solution, and 50 mL of 0.2 mol / L thiourea solution;

[0059] (2) stirring and mixing the aqueous ammonia solution and the aqueous silver nitrate solution to form a new solution;

[0060] (3) Then, the mixed solution obtained in step (2) was placed on a stirrer, and then the thiourea solution was added dropwise, and then the mixture was stirred (stirring speed was 1000 rpm) for 20 minutes to form a final product;

[0061] (4) extracting the product in step (3), washing it with deionized water three times, centrifuging it three times, and drying it (in an oven at 60° C.) to obtain silver sulfide;

[0062] (5) Weigh 5 mg of silver sulfide and 2 mg of nano-titanium dioxide, mix them in a beaker with ultrasonic stirring for 30 minutes;

[0063] (6) placing the material obtained in step (5) under a xenon lamp light source, stirring at a speed of 500 rpm, reacting for 1 hour, and then standing for 1 hour;

[0064] (7) Finally, the product obtained in step (6) was separated, rinsed with deionized water three times, and dried (drying temperature was 60° C., and drying time was 12 hours) to obtain a silver / silver sulfide-titanium dioxide composite catalyst.

[0065] Example 2

[0066] The electrocatalytic system adopts a traditional three-electrode system, that is, a platinum sheet electrode is selected as a counter electrode, a silver chloride electrode is selected as a reference electrode, and a catalyst film prepared from a thiol-modified silver / silver sulfide-titanium dioxide composite material is used as a working electrode. Before the electrocatalytic test, 50 ml of 0.1 mol / L potassium bicarbonate electrolyte is added to the cathode and cathode of the reaction cell, respectively, and the cathode cell is aerated at a flow rate of 60 sccm for 30 minutes to saturate the electrolyte. The flow rate is maintained at 30 sccm during the test. The three-electrode system is placed in a 0.1M potassium bicarbonate solution, and the electrocatalytic carbon dioxide reduction performance of the thiol-modified silver / silver sulfide-titanium dioxide composite is determined by linear scanning voltammetry under two different conditions of argon saturation and carbon dioxide saturation. The linear scanning voltammetry method determines the electrocatalytic carbon dioxide reduction performance of the thiol-modified silver / silver sulfide-titanium dioxide composite within a certain potential range (relative to RHE) and scanning rate. The potential range of the linear scanning voltammetry is -2.0 to 0.5 volts, and the scanning rate is 50 to 150 millivolts per second.

[0067] The preparation method of the working electrode is as follows: 2 mg of catalyst is dispersed in 0.1 mL of 15% isopropanol Nafion solution, and ultrasonicated for 30 minutes to form a uniform catalyst ink, and the ink is dropped on a 1×2 square centimeter carbon fiber paper to form a catalyst film with an effective area of ​​1 square centimeter. The catalyst film is connected with a conductive glue and a wire and used as a working electrode.

[0068] Figure 3 The current changes of silver nanoparticles, silver nanoparticles-titanium dioxide, silver / silver sulfide-titanium dioxide, thiol-modified silver sulfide and thiol-modified silver / silver sulfide-titanium dioxide composites under carbon dioxide and argon conditions are shown. Figure 3It can be obtained that compared with silver nanoparticles, silver nanoparticles-titanium dioxide, thiol-modified silver sulfide, and thiol-modified silver / silver sulfide-titanium dioxide have higher current density under carbon dioxide saturation. The current density of silver nanoparticles and thiol-modified silver sulfide decreases relative to silver / silver sulfide-titanium dioxide under carbon dioxide saturation. This is because silver nanoparticles and thiol-modified silver do not introduce titanium dioxide, and the active ingredients are easily lost or the specific surface area is not large enough, which affects its electrocatalytic performance. Silver nanoparticles or silver nanoparticles-titanium dioxide lack the synergistic effect between silver nanoparticles and silver sulfide relative to silver / silver sulfide-titanium dioxide, and the electrocatalytic performance of the two is not as good as silver / silver sulfide-titanium dioxide. The current density of thiol-modified silver / silver sulfide-titanium dioxide is not good under argon saturation, which shows that the catalyst has a stronger ability to inhibit hydrogen evolution reaction, and therefore shows high selectivity for carbon monoxide. The catalytic performance of silver / silver sulfide-titanium dioxide is not as good as that of thiol-modified silver / silver sulfide-titanium dioxide. This is because the synergistic effect of thiol-modified silver sulfide and titanium dioxide at the interface site can regulate the charge distribution, promote electron transfer, and also change the binding energy of the reaction intermediates, and can inhibit the occurrence of hydrogen evolution reaction. The product selectivity is optimized, thereby obtaining higher carbon dioxide reduction performance.

[0069] Example 3

[0070] The gas phase products were quantitatively analyzed by Fuli gas chromatograph (GC9790II) equipped with flame ionization detector (FID) and thermal conductivity detector (TCD). Ar was used as carrier gas, H2 was determined by TCD method, CO was determined by FID method, and a certain amount of standard gas was injected into the gas chromatograph to obtain the standard curves of H2 and CO. The product concentration was determined by CO method, the concentration of formate was analyzed by ion chromatography, and the standard curve of formate was obtained in 0, 5, 25, 50 and 100 ppm sodium formate standard solution. Under the condition of carbon dioxide saturation, the Faraday efficiency of each product of the electrocatalytic carbon dioxide reduction of thiol-modified silver / silver sulfide-titanium dioxide composite was detected.

[0071] Figure 3 The Faradaic efficiency distribution diagram of the products of the mercapto-modified silver / silver sulfide-titanium dioxide composite material under various potentials under carbon dioxide conditions is shown, and the material exhibits high selectivity for carbon monoxide. The Faradaic efficiency of carbon monoxide increases with the increase of the applied test potential, and at -1.3 V (vs. RHE), it exhibits the best Faradaic efficiency of 96.7%.

Claims

1. A silver-based composite catalyst, characterized in that The composite catalyst comprises Ag, thiol-modified silver sulfide and titanium dioxide. The thiol-modified silver sulfide is mixed with titanium dioxide so that the titanium dioxide is loaded on the thiol-modified silver sulfide with a lamellar structure. Then the thiol-modified silver sulfide is partially reduced to Ag, and the color of the material changes from white to gray to obtain the composite catalyst. The structural formula of the thiol-modified silver sulfide is as follows:

2. The silver-based composite catalyst according to claim 1, characterized in that When the mercapto-modified silver sulfide is mixed with titanium dioxide, the mass ratio of silver sulfide to titanium dioxide is 3-5:2-4.

3. A method for preparing the silver-based composite catalyst according to claim 1 or 2, characterized in that: The following steps are involved: (1) mixing a silver salt solution and a penicillamine solution to react and generate a white precipitate, which is then washed and dried to obtain thiol-modified silver sulfide; (2) mixing thiol-modified silver sulfide and nano-titanium dioxide to obtain a white suspension; (3) placing the white suspension obtained in step (2) under a xenon lamp light source for reaction, the white suspension slowly turns into gray to complete the reaction, washing, and drying to obtain the silver-based composite catalyst.

4. The method for preparing the silver-based composite catalyst according to claim 3, characterized in that: In step (1), the reaction temperature is 40-60°C.

5. The method for preparing the silver-based composite catalyst according to claim 3, characterized in that: In step (1), the silver salt is silver nitrate, and the concentrations of the silver nitrate solution and the penicillamine solution are both 0.2-1.5 mg / mL.

6. The method for preparing the silver-based composite catalyst according to claim 3, characterized in that: In step (2), the mercapto-modified silver sulfide and titanium dioxide are mixed by: mixing the mercapto-modified silver sulfide and nano-titanium dioxide and then ultrasonicating for 15 to 50 minutes.

7. The method for preparing the silver-based composite catalyst according to claim 3, characterized in that: In step (3), the reaction time is 0.5 to 2 hours.

8. Use of the silver-based composite catalyst according to claim 1 or 2 in catalyzing the reduction of CO2 to generate CO.

9. The use according to claim 8, characterized in that: The application method is as follows: electrocatalytic reduction of carbon dioxide is carried out in an H cell, the anode chamber comprises a counter electrode, the cathode chamber comprises a reference electrode and a working electrode, the two compartments are separated by an anion exchange membrane, and both sides are filled with KHCO3 solution as an electrolyte; wherein the working electrode is prepared by the silver-based composite catalyst.

10. The use according to claim 8, characterized in that: The preparation method of the working electrode is as follows: dispersing the silver-based composite catalyst in an isopropanol Nafion solution and ultrasonically forming a uniform catalyst ink, dropping the catalyst ink on carbon fiber paper to form a catalyst film, and connecting them with conductive glue and wires to serve as the working electrode.